2023
DOI: 10.3390/ijms24021181
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Simulation of Microgravity Induces Changes in Gene Expression in Breast Cancer Cells

Abstract: Microgravity changes the gene expression pattern in various cell types. This study focuses on the breast cancer cell lines MCF-7 (less invasive) and MDA-MB-231 (triple-negative, highly invasive). The cells were cultured for 14 days under simulated microgravity (s-µg) conditions using a random positioning machine (RPM). We investigated cytoskeletal and extracellular matrix (ECM) factors as well as focal adhesion (FA) and the transmembrane proteins involved in different cellular signaling pathways (MAPK, PAM and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 80 publications
(128 reference statements)
0
13
0
Order By: Relevance
“… PFC, 31 parabolas [ 189 ] MDA-MB-231 DEGs in MCS: AKT , KI67 , BCL2 , BAX , CD44 , and MMP9 after 72h; AKT , KI67 , BCL2 , and MMP9 after 24 h DEGs in RPM-AD: BAX , CD44 , and MMP9 after 72 h; BCL2 and MMP9 after 24 h RPM 24 h, 72 h [ 190 ] MCF-7, MDA-MB-231 qPCR-verified genes search in the mammalian phenotype database and the human genome-wide association studies (GWAS) Catalogue ERK1 , AKT1 , MAPK14 , EGFR , CTNNA1 , CTNNB1 , ITGB1 , COL4A5 , ACTB , and TUBB gene expression of MCSs differentially regulated in both cell types. 7 genes (ACTB, CD44, EGFR, ITGB1, PXN, TUBB, and VCL) were successfully analyzed using WCGNA RPM 14 d [ 191 ] Prostate cancer PC-3 3 d: Downregulation of VEGF , SRC1 , AKT , MTOR , and COL1A1 in MCS. No change in FLT1 , RAF1 , MEK1 , ERK1 , FAK1 , RICTOR , ACTB , TUBB , and TLN1 mRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… PFC, 31 parabolas [ 189 ] MDA-MB-231 DEGs in MCS: AKT , KI67 , BCL2 , BAX , CD44 , and MMP9 after 72h; AKT , KI67 , BCL2 , and MMP9 after 24 h DEGs in RPM-AD: BAX , CD44 , and MMP9 after 72 h; BCL2 and MMP9 after 24 h RPM 24 h, 72 h [ 190 ] MCF-7, MDA-MB-231 qPCR-verified genes search in the mammalian phenotype database and the human genome-wide association studies (GWAS) Catalogue ERK1 , AKT1 , MAPK14 , EGFR , CTNNA1 , CTNNB1 , ITGB1 , COL4A5 , ACTB , and TUBB gene expression of MCSs differentially regulated in both cell types. 7 genes (ACTB, CD44, EGFR, ITGB1, PXN, TUBB, and VCL) were successfully analyzed using WCGNA RPM 14 d [ 191 ] Prostate cancer PC-3 3 d: Downregulation of VEGF , SRC1 , AKT , MTOR , and COL1A1 in MCS. No change in FLT1 , RAF1 , MEK1 , ERK1 , FAK1 , RICTOR , ACTB , TUBB , and TLN1 mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…A recent long-term s-µg study demonstrated an association between the real metastatic microtumor environment and breast cancer cells (MCF-7, MDA-MB-231) exposed to the RPM with respect to biological factors related to the extracellular matrix, cytoskeleton, morphology and different cellular signaling pathways [ 191 ]. It was shown that the key elements ( ERK1 , AKT1 , MAPK14 , EGFR , CTNNA1 , CTNNB1 , ITGB1 , COL4A5 , ACTB and TUBB ) were differentially expressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They include ocularvestibular changes, blood clotting and wound healing dysfunction, increased cellular turnover and the more widely appreciated cardiovascular and musculo-skeletal changes [45][46][47]. There is good evidence to support gene dysregulation, immune dysfunction and disturbances in cellular and immune signaling as the contributors to some of these effects [48]. These effects may or may not be coupled with increased radiation exposure, from which the Earth's gravitational field currently provides humans with protection [49,50].…”
Section: The Physiological Effects Of Altered Gravity Environmentsmentioning
confidence: 99%
“…These changes occurred time-dependently and were dependent on the tumor type. In general, µg had impact on among others survival [195], apoptosis, adhesion, focal adhesion, migration, growth, the cytoskeleton, extracellular matrix, growth factors, several signaling pathways such as PAM, MAPK, and VEGF signaling [196][197][198].…”
Section: Breast Cancermentioning
confidence: 99%